Parameters for Site-Specific Soil Phosphorus Loss Modeling from Soil Test Data - Biswanath Dari; Vimala D. Nair; Willie G. Harris (EDIS, 2017)
This 4-page fact sheet is part of the Soil Phosphorus Storage Capacity (SPSC) for Phosphorus Risk Assessment and Management series. This series is intended for use by those who are interested in management practices and policies that minimize the risk of phosphorus loss from soils. Written by Biswanath Dari, Vimala D. Nair, and Willie G. Harris and published by the Department of Soil and Water Sciences, February 2017.